2008
DOI: 10.1007/s11999-008-0151-5
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Piriformis Syndrome After Surgical Release

Abstract: Piriformis syndrome is an uncommon condition characterized by sciatic nerve entrapment at the greater sciatic notch. Nonoperative treatment such as physical therapy, nonsteroidal antiinflammatory drugs, and local injections often results in relief of symptoms. For patients who do not benefit from nonoperative therapy, surgical exploration and decompression of the sciatic nerve has been effective. However, the success of surgery may be diminished by scar formation or hematoma in the anatomically restricted scia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 20 publications
0
5
0
1
Order By: Relevance
“…Surgical release is considered for individuals who do not respond to conservative methods. Recurrence after surgery for Piriformis muscle syndrome has been reported by Kobbe et al [ 2 ], and to the best of our knowledge, this is the second study addressing this subject.…”
Section: Introductionmentioning
confidence: 54%
See 2 more Smart Citations
“…Surgical release is considered for individuals who do not respond to conservative methods. Recurrence after surgery for Piriformis muscle syndrome has been reported by Kobbe et al [ 2 ], and to the best of our knowledge, this is the second study addressing this subject.…”
Section: Introductionmentioning
confidence: 54%
“…To the best of our knowledge, recurrent piriformis syndrome has been documented by Kobbe et al [ 2 ]. Our patient similar to the cases reported by Kobbe et al [ 2 ] had an anatomical variation of piriformis muscle and sciatic nerve.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…La ténotomie peut également se faire à ciel ouvert [6][7][8][9][10] avec un abord postérieur de la hanche. En plus du préjudice esthétique après décompression chirurgicale à ciel ouvert, Kobbe et al [16] rapportaient deux cas de récurrence de la symptomatologie causée par la formation de fibrose dans l'échancrure ischiatique. Aucune étude ne compare les résultats des deux techniques, aussi il est difficile de juger des avantages et inconvénients de chacune.…”
Section: Discussionunclassified
“…Posterior approach was used for traditional method, but it had to make a longer skin incision than our case for exposure of the piriformis muscle. After these traditional incisions, Kobbe et al [7] reported two cases of symptom recurrence after surgical decompression caused by scar formation of sciatic notch.…”
Section: Discussionmentioning
confidence: 99%